If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(q + -4) = 64 Reorder the terms: 6(-4 + q) = 64 (-4 * 6 + q * 6) = 64 (-24 + 6q) = 64 Solving -24 + 6q = 64 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 6q = 64 + 24 Combine like terms: -24 + 24 = 0 0 + 6q = 64 + 24 6q = 64 + 24 Combine like terms: 64 + 24 = 88 6q = 88 Divide each side by '6'. q = 14.66666667 Simplifying q = 14.66666667
| 4x^2-9x+9=3x+4 | | 2/5(5x-15)=4 | | f(x)=x^3+16x^2-19x-10 | | r-(-1.2)=7.3 | | 5m+6m+8m-5= | | 6(4-2e)-3(5+3e)= | | b+5b=42 | | 54/3^2*6(6-3) | | 13c-52= | | 6x+33=16x+3 | | 4r-1whenr=9 | | 4.6x-12.1=10.9 | | 8r^2=18+18r | | 93-4x=4x-5 | | 4x+9=-67 | | X+5Y=2X+Y | | -9+3(7y-8)=4(-3y+3)+5 | | 4x-9=-67 | | (x/4)^2-225=(150-x/4)^2 | | m/4+6=m/3+8 | | x^4-7x^3-30x^2=0 | | 1/2r+6=5 | | 6p - 5=2p+7+7 | | 5t-18=12+3x | | 1+4i/4-i | | -7x-16=-5x | | 15p^2=20+20p | | 3y/8-9=y/8 | | 10q+3(5-2q)+4(7q+4)= | | 5x/-4=6x/8 | | 4/15z=1/10-4/9 | | 2x+1x+1x=180 |